The The Impact of Using Tutorial Videos Uploaded on Youtube Platform toward the Students’ Learning Motivation and Their English Learning Outcomes - Pravitasari, Suryanti Galuh; Vulandari, Retno Tri (International Journal of English Linguistics, Literature, and Education (IJELLE), 2023)
This research was aimed at finding out whether the use of tutorial videos uploaded on the YouTube platform can increase the learning outcomes and the learning motivation of the students. This research was categorized into quantitative experimental design types by providing a pretest before giving the students treatment using tutorial videos uploaded on YouTube during the teaching and learning process and a post-test after the treatment. The object of the research was the third-semester students of STMIK Sinar Nusantara Surakarta who were taking English III which was designed for the TOEFL Preparation Test. The 60 respondents were selected by using a simple random sampling technique. The data collection was taken from the results of the pre-post tests and the result of the questionnaire concerning the students’ learning motivation using the tutorial media on YouTube and their opinions about the videos. The average score of the pre-test was 61 while the average score of the post-test was 82. Therefore it can be concluded that the use of the tutorial video uploaded on Youtube is considered effective in helping the students to increase their learning outcomes. Meanwhile, the use of tutorial videos uploaded on Youtube has a regression coefficient value of 0.306 which means that it has a positive influence on Learning Motivation. Therefore, it can be concluded that learning English for TOEFL's Grammar test preparation by watching tutorial videos on Youtube is effective to increase the student’s English learning motivation hence increasing their learning outcomes.